2013
DOI: 10.1007/s40477-013-0052-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-treatment sequential ultrasound imaging of follicular cyst in a crossbred dairy cow

Abstract: Several studies in dairy cattle have investigated the final outcome of different treatment regimens in follicular cyst condition. However, sequential monitoring of the response of follicular cysts to these treatments is rather scanty. In this paper, we present the response of a large follicular cyst in a pluriparous crossbred dairy cow with prolonged conception failure to human chorionic gonadotropin, hCG (3,000 IU; day 0) and cloprostenol (500 lg; day 9) treatment. Using transrectal ultrasonography (USG), rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In the present study, a significant regression of the refractory COFs was observed in the hCG-3 group on day 7 compared to the other groups, indicating that the repeated administration of low dose hCG may be more effective in regressing COFs. A dose of 3,000 IU hCG resulted in the development and selection of new dominant follicles 4 days after treatment ( 11 ). The number of follicles < 4 mm in diameter increased after administration of hCG in groups hCG-2 and hCG-3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, a significant regression of the refractory COFs was observed in the hCG-3 group on day 7 compared to the other groups, indicating that the repeated administration of low dose hCG may be more effective in regressing COFs. A dose of 3,000 IU hCG resulted in the development and selection of new dominant follicles 4 days after treatment ( 11 ). The number of follicles < 4 mm in diameter increased after administration of hCG in groups hCG-2 and hCG-3.…”
Section: Discussionmentioning
confidence: 99%
“…Under field conditions, the diagnosis of COFs is based on behavioral abnormalities, transrectal examination of the genital tract including ultrasonography (US), and occasionally, blood progesterone (P4) profiles. Different treatment regimens involving gonadotropin releasing hormone (GnRH), human chorionic gonadotropin (hCG), prostaglandin F2α (PGF2α), and P4 have been used with variable ovarian responses and cure rates ( 2 , 10 , 11 ). Human chorionic gonadotropin has been used to successfully treat COFs non-responsive to GnRH ( 2 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Follicle diameter measurements are carried out with the help of an electronic capillary on ultrasonography by measuring the length of the diameter of the horizontal line and vertical edge of the follicle and then averaging it. This study measured follicular development to Graafian follicles (Khan et al 2015).…”
Section: Methodsmentioning
confidence: 99%